Progression of HTLV-1 Associated Myelopathy/Tropical Spastic Paraparesis after Pregnancy: A Case Series and Review of the Literature - Frederique A. Jacquerioz; Mauricio La Rosa; Elsa González-Lagos; Carolina Alvarez; Martin Tipismana; Karen Luhmann; Eduardo Gotuzzo (Pathogens)
HTLV-1-associated Myelopathy/Tropical Spastic Paraparesis (HAM/TSP) is a progressive non-remitting and incapacitating disease more frequently seen in women and with a patchy worldwide distribution. HAM/TSP develops in a small percentage of HTLV-1-infected individuals during their lifetime and etiologic factors for disease progression are still unclear. This study aims to describe the first case series of the progression of HAM/TSP in relation to pregnancy. Between January and March of 2012, we reviewed medical charts of women with HAM/TSP currently enrolled in the HTLV-1 cohort at the institute of tropical medicine of Cayetano Heredia University. Inclusion criteria included having a diagnosis of HAM/TSP according to the WHO guidelines and self-reported initial symptoms of HAM/TSP during pregnancy or within six months of delivery. Fifteen women reported having had symptoms compatible with HAM/TSP within four months of delivery. Among them, ten women had no symptoms before pregnancy and reported gait impairment after delivery. Five women with mild gait impairment before pregnancy noticed a worsening of their symptoms after delivery. Symptoms worsened after successive pregnancies. Recent studies have shown that HTLV-1 infection induces a strong T cell-mediated response and that the quality of this response plays a role in HAM/TSP pathogenesis. The relative immunosuppression during pregnancy, including blunting of the T-cell response, might allowed in certain women enhanced replication of HTLV-1 and disease progression in the postpartum. This is the first study looking specifically at HAM/TSP and pregnancy and the number of cases is remarkable. Further prospective studies of HTLV-1-infected women assessing immune markers during pregnancy are warranted. Breastfeeding was the main route of transmission. Strategies to prevent vertical transmission need to be evaluated in HTLV-1 endemic countries of Latin America.